The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-11511-7
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment with Tempol during acquisition or withdrawal from CPP abolishes the expression of cocaine reward and diminishes oxidative damage

Abstract: In previous studies, we reported that pretreatment with the antioxidant Tempol attenuated the development and expression of cocaine-induced psychomotor sensitization in rats and diminished cocaine-induced oxidative stress (OS) in the prefrontal cortex (PFC) and nucleus accumbens (NAc), suggesting a potential role for Tempol in interfering with cocaine-related psychomotor sensitization. The aim of the current study was to examine the role of Tempol in reward and reinforcement using the conditioned place prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…Its own degradation products, including norcocaine and norcocaine derivatives (nitroxide radical, N-hydroxy, nitrosonium, cocaine iminium, and formaldehyde), also have relatively higher oxidation potentials and result in stronger lipid peroxidation than cocaine induced itself [ 31 ]. Elevated oxidative stress has been well demonstrated in acute and chronic models of cocaine administration [ 32 , 33 ]. On the other hand, cocaine suppresses the expression and abolishes the activity of endogenous antioxidant enzymes and non-enzymatic antioxidants.…”
Section: The Neurotoxicity Of Cocainementioning
confidence: 99%
“…Its own degradation products, including norcocaine and norcocaine derivatives (nitroxide radical, N-hydroxy, nitrosonium, cocaine iminium, and formaldehyde), also have relatively higher oxidation potentials and result in stronger lipid peroxidation than cocaine induced itself [ 31 ]. Elevated oxidative stress has been well demonstrated in acute and chronic models of cocaine administration [ 32 , 33 ]. On the other hand, cocaine suppresses the expression and abolishes the activity of endogenous antioxidant enzymes and non-enzymatic antioxidants.…”
Section: The Neurotoxicity Of Cocainementioning
confidence: 99%
“…The NAc projects to motor areas such as the ventral pallidum, which externalizes these abnormally enhanced memories into addiction-related behaviours, such as compulsive drug-seeking behaviour. 8 Furthermore, the pharmacological manipulation of the NAc markedly affects the acquisition and expression of conditioned responses, 9,10 indicating that the NAc has a critical role in cue-reward learning.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we studied the effect of Tempol on cocaine conditioned reward using the conditioned place preference (CPP) paradigm (Box 1). We demonstrated that injection of Tempol together with cocaine during acquisition of CPP attenuated the expression of CPP measured one day following conditioning 36 . We found that OS was significantly elevated following the establishment of CPP, and that cocaine-induced OS was significantly diminished by pretreatment with Tempol during conditioning.…”
Section: Drug Self-administration (Sa)mentioning
confidence: 80%